Estrification of Acetic Acid with Isoamyl Alcohol over Expandable Graphite Catalyst - Xiu-Yan Pang; Pu Lv; Yi-Shuang Yang; Hai-Li Ren; Fei Gong (E-Journal of Chemistry)
The catalysis of expandable graphite for esterification of acetic acid with isoamyl alcohol has been studied. Expandable graphite was prepared with three different methods. In esterification reaction, the influences of catalyst amount, materials ratio, reaction time, prepared method of the expandable graphite on esterification reaction were discussed. X-ray diffraction spectrum of expandable graphite testified the existence of H2SO4 intercalation reaction. Through L9(34) orthogonal experiment, optimum esterification reaction conditions were gained as: n(isoamyl alcohol):n(acetic acid)=1.5:1, w(catalyst with a expandable volume of 290 mL•g-1) = 7.5% total amount of materials, reaction time 1.5 h, and temperature keeping at the boiling point. Yield of isoamyl acetate reachs 96.0%. It was testified that expandable graphite was a kind of effective catalyst in the esterification of acetic acid with isoamyl alcohol.